Reinforcing carbonized polyacrylonitrile fibers with nanoscale graphitic interface-layers. (30th December 2021) - Franklin, Rahul; Xu, Weiheng; Ravichandran, Dharneedar; Jambhulkar, Sayli; Zhu, Yuxiang; Song, Kenan
Abstract: Carbon fibers going through stabilization, carbonization, and graphitization heat-treatment stages will form continuous graphitic layers that are closely packed and preferentially aligned along the fiber axis, forming high mechanical stiffness or strength and electrical or thermal conductivity. The alignment of noncontinuous, powder-like graphene layers in polymers has been challenging due to the low bending modulus of a few- or even single-layered graphene, which causes aggregations or folding behaviors. This research demonstrates the leveraging of polymer-nanoparticle interactions to align graphene nanoplatelets (GNPs) in the polyacrylonitrile (PAN) matrix. An in-house designed spinning method produces a three-layered fiber that utilizes the interfacial interactions between each layer for graphene alignment between graphitic layers. This composite containing oriented GNPs significantly improves modulus (i.e., 42.3 to 74.6 GPa) and increases electrical conductivity for enhancing volatile organic compounds (VOCs) sensing behaviors. This research opens up a new scalable fabrication method for multilayered composites. Graphical abstract: Image, graphical abstract